Board Capitals, R&D and Leverage Strategies on Financial Performance - Yeh, Li-Jen; Kuo, Hsien-Chang (Business and Economic Research, 2021)
<p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Exactly how corporate boards influence their firms’ performance remains a puzzle. We construct a mediational model to observe the paths that board capitals affect firm’s key strategies (as R&D and leverage). Furthermore, we can estimate the direct and mediational influent level of board capitals on financial performance. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">For confirming those hypotheses in our study, the financial data of listed companies in Taiwan and Mainland China are collected. This study confirms that the education level and seniority of firm’s directors significantly influence the R&D intensity and financial leverage of corporates, furthermore affect firm performance. This mediational effects from R&D intensity and debt ratio are estimated about 22.31%~35.65% in Taiwan, and 25.46%~39.47% in Mainland China. We also find that the higher education level and the less seniority of the Boards lead to the more R&D intensity and the less debt ratio, then the better financial performance.